A preliminary assessment of the carbon footprint of households in Greece. (2015) - Angelakoglou, Komninos; Aktsoglou, Despoina; Gaidajis, Georgios; Margiolaki, Ioanna; Tzomaka, Vasiliki
The carbon footprint deriving from the consumption needs of four households in Greece was estimated in the specific study. The specific households were chosen in order to represent different occupational and spatial profiles. A three-step method was developed to determine the relative carbon dioxide equivalent (CO2eq ) emissions. Various inputs and outputs of the examined system (i.e., food, clothing, electricity, heating oil) were recorded and translated into carbon footprint with the application of the Intergovernmental Panel for Climate Change (IPCC) global warming potential (GWP) impact assessment method (IPCC 2007 GWP 100a method) and the utilisation of relative life cycle assessment software. Results indicated that, in the observed period, products and electricity consumption were the key factors affecting the carbon footprint (>50%) of the households examined. Furthermore, heating needs were responsible for over 25% of the total household emissions. The carbon footprint expressed in tons CO2eq, ranged from 5.7 to 7.5 per person per year, indicating that households behaviour varies considerably in terms of responsible attitudes regarding sustainable consumption.